Behavioral Compliance and Psychosocial Support as Determinants Mental Health among Adolescents during COVID-19 Pandemic in Kenya - Joan Mukami (IJRDO- Journal of Educational Research, 2021)
Covid-19 pandemic that is raging around the globe has caused unmatched behavioral ‘shock effects’ in various facets of human activity. The impact on adolescents is unprecedented. According to the UNESCO (2020) statistics released on 9 April 2020, there are over 1,500,000,000 learners globally from primary to higher learning institutions who are not attending school. Following the closure of learning institutions, banned recreational activities, and separation from friends, feelings of stress, anxiety, and uncertainty among young people are inevitable. Undeniably, the spread of COVID-19 has adversely affected the education system globally. To curb the problem, different countries have indeed introduced an array of policies that range from complete closure in Italy and Germany to targeted closure in the United Kingdom. In the education sector, over 100 countries have imposed nationwide closure of schools, and Kenya is not exceptional. While the intention to close the learning institutions is to prevent further spread of the virus within institutions, the closure has had widespread psychological implications to the adolescents.